CALCIUM/CALMODULIN DEPENDENT PROTEIN KINASE II δ MODULATES INTRACELLULAR Ca2+ RELEASE AND CELL PROLIFERATION IN ADULT CARDIAC FIBROBLASTS. (21st November 2014) - Salleh, M Mohd; McCluskey, C; Bushell, T; Currie, S
Abstract : Calcium/calmodulin dependent protein kinase II δ (CaMKIIδ) is a well-recognised mediator of cardiomyocyte function and dysfunction, however little is known of its role in the cardiac fibroblast (CF). [Ca2+]i plays a crucial role in cell proliferation, yet the mechanism by which this is regulated in adult CFs remains elusive. We hypothesised that CaMKIIδ can regulate intracellular Ca2+ release channel activity and proliferation in adult CFs. Using Fura-2 loaded cells, we initially confirmed agonist-mediated intracellular Ca2+ release using Angiotensin II (1 µM). We demonstrated that CaMKIIδ and Inositol 1, 4, 5-triphosphate receptor type 2 (IP3R2) are both highly expressed in adult rat CFs but the ryanodine receptor (RyR2) is not. This identifies IP3R2 as the main intracellular Ca2+ release channel in these cells. To investigate whether CaMKIIδ modulates IP3R activity in CFs, cells were pre-treated with inhibitors autocamtide inhibitory peptide (AIP) (1 µM) and KN-93 (5 µM) prior to Angiotensin II application. Ca2+ release was significantly inhibited in the presence of both inhibitors (81±6.5% (AIP) vs 123±6% (control), p<0.001, n=4 and 65±4% (KN-93) vs 123±6% (control) respectively, p<0.001, n=4). Both CaMKII inhibition and IP3R inhibition also inhibit CFs proliferation (∼10% and 30% inhibition, AIP and 2-APB treatments respectively). The possibility that Ca MKIIδ may modulate IP3R2 activity directly via protein-protein interaction has also been explored using co-immunoprecipitation. Collectively, this study reveals for the first time that CaMKIIδ modulates intracellular Ca2+ release and proliferation in adult CFs and more specifically, that this may be modulated via physical interaction between CaMKIIδ and IP3R2.